Challenges Associated with the Expansion of Deposit Insurance Coverage during Fall 2008 - Sebastian T. Schich (Economics: The Open-Access, Open-Assessment E-Journal, 2009)
Government provision of a financial safety net for financial institutions has been a key element of the policy response to the current crisis, with governments extending existing guarantees and introducing new ones. These measures have been helpful in avoiding a further accelerated loss of confidence. But they are not costless. Like any guarantee, deposit insurance gives rise to moral hazard, especially if the coverage is unlimited. In the midst of a crisis, the immediate task is to restore confidence, and guarantees can be helpful in that respect. Nonetheless, to keep market discipline operational, it is important to specify when the extra insurance will end, and this timeline needs to be credible. To be able to establish such a timeline the root causes of the lack of confidence - that is the effects of troubled assets on financial firms' health - need to be addressed effectively. On a more fundamental level, once a government has ventured down the road of guarantee expansion, there may be a general perception that a government guarantee will always be available during crisis situations. As a consequence, other elements of the financial safety net may need to be strengthened, including the prudential and supervisory framework.
Keywords: E61; G01; G22; 330; Policy responses to financial crisis; safety net; deposit insurance; moral hazard; Einlagensicherung; Bürgschaft; Öffentliche Kreditvergabe; Finanzmarktkrise; Moral Hazard; Welt